Learning to teach - Arends, Richard I. (McGraw-Hill Book Company, 1988)
Provides comprehensive coverage of general teaching methods and models. By covering all major teaching models plus the leadership of teaching, including planning, classroom management, assessment, motivation, and management of time and space, this book helps future teachers master both the theory and application of successful teaching.